Leptin modifies the prosecretory and prokinetic effects of the inflammatory cytokine interleukin‐6 on colonic function in Sprague–Dawley rats. Issue 12 (11th November 2016) - Buckley, Maria M.; O'Brien, Rebecca; Devlin, Michelle; Creed, Aisling A.; Rae, Mark G.; Hyland, Niall P.; Quigley, Eamonn M. M.; McKernan, Declan P.; O'Malley, Dervla
Abstract : New Findings: What is the central question of this study? Does crosstalk exist between leptin and interleukin‐6 in colonic enteric neurons, and is this a contributory factor in gastrointestinal dysfunction associated with irritable bowel syndrome? What is the main finding and its importance? Leptin ameliorates the prosecretory and prokinetic effects of the pro‐inflammatory cytokine interleukin‐6 on rat colon. Leptin also suppresses the neurostimulatory effects of irritable bowel syndrome plasma, which has elevated concentrations of interleukin‐6, on enteric neurons. This may indicate a regulatory role for leptin in immune‐mediated bowel dysfunction. In addition to its role in regulating energy homeostasis, the adipokine leptin modifies gastrointestinal (GI) function. Indeed, leptin‐resistant obese humans and leptin‐deficient obese mice exhibit altered GI motility. In the functional GI disorder irritable bowel syndrome (IBS), circulating leptin concentrations are reported to differ from those of healthy control subjects. Additionally, IBS patients display altered cytokine profiles, including elevated circulating concentrations of the pro‐inflammatory cytokine interleukin‐6 (IL‐6), which bears structural homology and similarities in intracellular signalling to leptin. This study aimed to investigate interactions between leptin and IL‐6 in colonic neurons and their possible contribution to IBS pathophysiology. The functional effects of leptin and IL‐6 on colonic contractility and absorptosecretory function were assessed in organ baths and Ussing chambers in Sprague–Dawley rat colon. Calcium imaging and immunohistochemical techniques were used to investigate the neural regulation of GI function by these signalling molecules. Our findings provide a neuromodulatory role for leptin in submucosal neurons, where it inhibited the stimulatory effects of IL‐6. Functionally, this translated to suppression of IL‐6‐evoked potentiation of veratridine‐induced secretory currents. Leptin also attenuated IL‐6‐induced colonic contractions, although it had little direct effect on myenteric neurons. Calcium responses evoked by IBS plasma in both myenteric and submucosal neurons were also suppressed by leptin, possibly through interactions with IL‐6, which is elevated in IBS plasma. As leptin has the capacity to ameliorate the neurostimulatory effects of soluble mediators in IBS plasma and modulated IL‐6‐evoked changes in bowel function, leptin may have a role in immune‐mediated bowel dysfunction in IBS patients. Abstract :